1991
DOI: 10.1111/j.1469-8137.1991.tb00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of vesicular‐arbuscular mycorrhiza formation and growth of white clover by flavonoid compounds

Abstract: SUMMARYThe effects of flavonoid compounds on VA mycorrhiza root colonization and growth of w-hite clover {Trifolium repens L.) plants under growth chamber conditions are reported. The isoflavonoids, formononetin and biochanin A, previously identified from clover roots, stimulated colonization and growtb of clover, while several other flavonoid compounds were inactive when tested at concentrations of 5 mg 1"', The flavone, chr\'sin, wben applied 3t concentrations higher than those tested for formononetin and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
16

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(104 citation statements)
references
References 36 publications
6
79
1
16
Order By: Relevance
“…No nível mais alto de contaminação, a colonização foi reduzida em 75% em relação ao solo controle sem contaminantes, mesmo na presença de formononetina. No solo não contaminado, a aplicação dessa substância aumentou em quase 50% a colonização das raízes, confirmando os resultados de vários outros estudos com estes flavonóides em milho (Siqueira et al, 1991b;Silva Jr. & Siqueira, 1997). No entanto, esses incrementos diminuíram com a elevação da proporção de solo contaminado, sendo inexistente a 10%.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…No nível mais alto de contaminação, a colonização foi reduzida em 75% em relação ao solo controle sem contaminantes, mesmo na presença de formononetina. No solo não contaminado, a aplicação dessa substância aumentou em quase 50% a colonização das raízes, confirmando os resultados de vários outros estudos com estes flavonóides em milho (Siqueira et al, 1991b;Silva Jr. & Siqueira, 1997). No entanto, esses incrementos diminuíram com a elevação da proporção de solo contaminado, sendo inexistente a 10%.…”
Section: Resultsunclassified
“…Como discutido em trabalhos já citados, a colonização micorrízica pode amenizar o estresse da fitotoxidez de metais e, à semelhança do que tem sido demonstrado para estresse induzido por resíduo de herbicida no solo (Siqueira et al, 1991b), a aplicação dessa substância pode favorecer o crescimento de plantas em solo com excesso de metais. Isto foi objeto do presente estudo, que utilizou o milho como planta-teste.…”
Section: Introductionunclassified
“…Mycorrhizal fungi may have evolved to use the most abundant flavonoid to induce hyphal branching and stimulate colonization. Other studies either failed to identify an effect of genistein on hyphal growth (Baptista and Siqueira, 1994) and root colonization (Siqueira et al, 1991) or have even indicated an inhibition of the fungal development (Chabot et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1990s, Nair et al (1991) and Siqueira et al (1991) found that some chemical substances were able to act as biochemical signals and as mycorrhizal colonization stimulants of native arbuscular mycorrhizal fungi, such as isoflavonoid formononetin . These stimulants are alternatives to maximize benefits in the nutritional improvement of plants and in the reduction of biotic and abiotic stresses.…”
Section: Palavras-chavementioning
confidence: 99%